2016
DOI: 10.1371/journal.pone.0161352
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Salmonella enterica Serovar Aberdeen Negative for H2S Production in China

Abstract: Salmonella enterica infections continue to be a significant burden on public health worldwide. The ability of S. enterica to produce hydrogen sulfide (H2S) is an important phenotypic characteristic used to screen and identify Salmonella with selective medium; however, H2S-negative Salmonella have recently emerged. In this study, the H2S phenotype of Salmonella isolates was confirmed, and the selected isolates were subjected to antimicrobial susceptibility testing and molecular identification by multilocus sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…However, the phs operon is essential for this activity in Salmonella [ 24 ]. Sakano et al [ 8 ] detected a nonsense mutation in the phsA gene in H 2 S-negative S. Infantis and S. Typhimurium isolates, and in our previous studies, we found more mutations in the phsA gene of H 2 S-negative S. Senftenberg, S. Choleraesuis, and S. Aberdeen [ 13 15 ]. These data suggest that the disruption of the phs locus is responsible for the lack of H 2 S production and incorrect identification of Salmonella .…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, the phs operon is essential for this activity in Salmonella [ 24 ]. Sakano et al [ 8 ] detected a nonsense mutation in the phsA gene in H 2 S-negative S. Infantis and S. Typhimurium isolates, and in our previous studies, we found more mutations in the phsA gene of H 2 S-negative S. Senftenberg, S. Choleraesuis, and S. Aberdeen [ 13 15 ]. These data suggest that the disruption of the phs locus is responsible for the lack of H 2 S production and incorrect identification of Salmonella .…”
Section: Introductionsupporting
confidence: 77%
“…Previous studies have reported mutations in the phs operon may responsible for the non-H 2 S-producing phenotype in Salmonella [ 8 , 13 15 ] . In the phsA gene, three different mutation sites were detected among the 46 H 2 S-negative Salmonella isolates (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonellosis due to this serovar has mostly affected children but it has also caused disease in adults (Ghoddusi et al 2015). More than 2700 serotypes of Salmonella have been reported (Wu et al 2016). Studies have shown S. Infantis as predominantly present in the poultry industry worldwide (Fuche et al 2016) and cause substantial economic losses (Rajagopal and Mini 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this has not been demonstrated for the S . Typhimurium specific PHS pathway, even though this is considered the main source of H 2 S in this species [23,24]. Therefore, we carried out various antimicrobial susceptibility tests (S1 Fig, Error!…”
Section: Resultsmentioning
confidence: 99%